UPAYA KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MADRASAH TARBIYAH ISLAMIYAH JAHO - Yunelda Yunelda (IAIN Batusangkar, 2018)
The purpose of this study to determine the headmaster efforts in improving the performance of teachers in the madrasas tarbiyah islamiyah jaho. This study user a qualitative method using fenomologi perspective. Data collection techniques such as observation, interviews adn documentation study. Subjec this study headmaster, administration and teacher of Madrasas Tarbiyah Islamiyah Jaho. As for test data by tringulasi, tchniques of data analysis with qualitative descriptive analysis. As for the result of this study Were (1) the efforts headmaster ini improving the performance of teacher in the field of lessin plans that inculde teacher Training or Training event and Activities MGMP. (2) efforts headmaster in improving teacher performance in the implementation of learning is that the Monitoring and Supervision with Supervision. (3) attempts headmaster in improving teacher performance evaluation in the field of learning that check book value of teacher and teacher analysis of Daily tests.